Safety Assessment of Composite Cylinders for Gas Storage by Statistical Methods Potential for Design Optimisation Beyond Limits of Current Regulations and Standards - Mair, Georg W. (Springer International Publishing : Imprint: Springer, 2017)
XXI, 369 p. 242 illus., 231 illus. in color.